TO DEVELOP THE QUALITIES OF RESPONSIBILITY AND INITIATIVE IN FUTURE TEACHERS' SOCIO-SPIRITUAL ACTIVITIES (Web of Teachers: Inderscience Research, 2025)
In modern society, the upbringing of the qualities of responsibility and initiative in the process of socialization of a person is an important scientific and practically necessary pedagogical problem. This scientific concept is the subject of research in several fields of science and several areas of theoretical psychological science. Several factors of studying the sense of responsibility of a person in the process of socialization are the object of research in the sciences of philosophy, sociology, psychology and pedagogy.